Hubungan antara Nyeri Fraktur dengan Kualitas Tidur Pasien yang di Rawat Inap - Juli Andri; Panzilion Panzilion; Tri Sutrisno (Jurnal Kesmas Asclepius, 2019)
This study aims to determine the relationship between fracture pain and sleep quality. This research was conducted in the Seruni room of Dr. M. Yunus Bengkulu and in the Seruni room at Bhayangkara Hospital TK III Bengkulu. The research design used was correlational using a cross sectional approach. The results of the univariate analysis showed that (73.3%) respondents had poor sleep quality and (60%) had severe fracture pain intensity. The results of bivariate analysis with correlation test obtained p-value = 0.002 (p <0.05). In conclusion, there is a relationship between fracture pain and the sleep quality of patients hospitalized at the hospital in Bengkulu Province. Keywords: Fracture Pain, Sleep Quality